Analysis of Brand Identity Gontor Islamic Boarding School in Official Youtube Channel - Zulaikha Zulaikha; Nur’annafi Farni Syam Maella; Farida Farida (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
Gontor Islamic Boarding School is the largest modern Islamic boarding school in Indonesia. Even though it is touted as the number one Islamic boarding school, Gontor still communicates his institution on social media. This is interesting because so far, there has been an assumption that Islamic boarding schools are closed Islamic educational institutions and severely restrict access to information. Therefore, the problem raised in this study is how the analysis of the brand identity of the Gontor Islamic boarding school is displayed on the official Youtube account of the Gontor Islamic boarding school. The purpose of this study is to find out what brand identities are displayed, how to display them and whether each show that contains multiple brand identities also has high engagement. From the results of the analysis of the data obtained, it will be seen how the largest Islamic boarding school in Indonesia builds its brand identity on social media, especially Youtube. The results of this study are useful for other Islamic boarding schools, or other religious educational institutions to build institutional branding through social media, especially Youtube. It can also be an example of how religious education institutions can communicate themselves and how Islamic boarding schools can become part of the information society. The choice of brand identity or brand identity in the research theme of this Islamic boarding school, because not many have done professional branding in Islamic boarding schools. Showing an honest brand identity is the basic foundation in building a product brand. There are five elements of brand identity, namely place image (in the form of reputation), materiality, institutions (law, regulation, organization), relations (power, class, gender) and society and its culture (tradition, daily life). These five things are indicators in this study. Keywords: Islamic Boarding School, Brand Identity, Official Account, Youtube.